Modalities of Sutinah's Victory In Regional Head Elections In Mamuju Regency - Ahmad, Ardiansyah; Hardi, Rudi; Khaerah, Nur (Journal of Contemporary Local Politics, 2022)
The purpose of this research is to find out the Modality of Sutinah's victory in regional head elections in Mamuju Regency. The research method used is descriptive qualitative analysis, namely to obtain an in-depth picture of the role of the winning modality in the post-conflict local election in Mamuju district, and the type of research used is descriptive qualitative. The data sources used are primary data sources and secondary data from six main informants. Data collection techniques using the methods of observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion. The results of the research conducted show that there are three indicators in the modality of Sutinah's victory in the regional head election in Mamuju Regency, namely, political capital, social capital, and economic capital. This proves that Sutinah Suhardi, as a woman and also a migrant, was able to accumulate the capital she owned so that she succeeded in winning the Mamuju regional head election in 2020.